Effect of Manufacture of Industrial and Agricultural Waste By-Products on the Strength of Geopolymer Mortar (Comprehensive Journal of Science, 2025)
Recent research in the field of concrete and construction materials has shifted toward manufacturing an alternative to cement, which is geopolymer, considered an effective and environmentally friendly substitute. The primary focus of this work was to use solid waste materials from industrial and agricultural sources as a binding agent for each type of geopolymer mortar. In this study, we have three materials: palm oil waste (u-POFA), fly ash from power plants (FA), and blast furnace slag (GBFS). Standard cubes were made and tested at 3, 7, 14, and 28 days to investigate the geopolymer mortar. We observe a higher increase in the calcium-rich GBFS samples compared to the FA and u-POFA samples. The range of strength obtained for the samples was respectively from 14.67 to 38.30 (N/mm²) for u-POFA, from 34.10 to 56.82 (N/mm²) for FA, and from 66.89 to 83.44 (N/mm²). The properties of the samples were validated thru (XRD) analyzes. The results show that the main bonding phases consist of aluminum silicate crystals, calcium silicate hydrate (C–S–H), and aluminum and calcium silicate hydrate (C–A–S–H).
Keywords: : Industrial and agricultural materials Waste; Material (u-POFA), (FA), and (GGBS), Compressive Strength; X-ray diffractography (XRD).